PENGENALAN MICROSOFT PROJECT PADA PENGURUS MASJID AL-WAQIFIN ISLAMIC VILLAGE TANGERANG - Firdaus, Mohamad; Indra Bakti (Jurnal Padamu Negeri, 2024)
The training and introduction to Microsoft Project aim to enhance project management skills among the administrators of Al-Waqifin Mosque, Islamic Village, Tangerang. Microsoft Project is a software tool that facilitates effective management of time, resources, and budgets for various projects, including construted through ineractive training sessions that covered an introduction to key features, usage simulations, and discussions on practical implementation. The results of this activity demonstrated an increase in participants' understanding and ability to manage projects using a more structured and professional approach. Thia positive impact is expected to the efficiency and success of project implementation at Al-Waqifin Mosque.